Strategi Komunikasi Pemasaran (IMC) dalam Membangun Brand Image Merek Parfum Lokal "Reverseas" - Rizky, M. Daffa Ar; Mustika, Ratih Pandu (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze the Integrated Marketing Communication (IMC) strategy implemented by the local perfume brand Reverseas in building its brand image amid the increasingly competitive Indonesian perfume industry. The research was conducted in Surabaya, using a qualitative descriptive approach. Data collection was carried out through in-depth interviews and documentation studies involving seven informants, consisting of five internal informants and two external informants. The internal informants include the managerial team and marketing staff of Reverseas, while the external informants are active consumers of Reverseas products. The findings reveal that Reverseas applies an integrated communication strategy based on digital marketing, brand collaboration, and community-based marketing to strengthen its brand image and create emotional connections with urban youth consumers. The IMC strategy includes the use of social media, cross-industry collaborations, experiential marketing through “The Lab” stores, and consistent brand messaging that highlights local values and sustainability. The results confirm that the application of an integrated IMC approach can enhance brand awareness, foster customer loyalty, and solidify Reverseas' position as a local perfume brand with a strong identity and emotional relevance.